2010
DOI: 10.1016/j.janxdis.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The moderated effects of video feedback for social anxiety disorder

Abstract: Despite initially positive results, video feedback for social anxiety has never been shown to reduce social anxiety in a controlled experiment with diagnosed participants, and only once with undiagnosed participants. Previous studies arguably did not detect such an effect because of limited assessment of anxiety and potential moderators. We tested video feedback with cognitive preparation among treatment-seeking participants with a primary diagnosis of social anxiety disorder. In Session 1, participants gave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 28 publications
6
38
1
Order By: Relevance
“…disorder severity, sociodemographic characteristics) in order to allow for conclusions to be drawn across multiple anxiety disorders. Based on these criteria, we excluded papers that measured variables after baseline (Burton, Schmertz, Price, Masuda, & Anderson, 2013;Rodebaugh, Heimberg, Schultz, & Blackmore, 2010) or only conducted withingroup analyses (Andersson, Carlbring, & Grimlund, 2008;Brody et al, 1998;Cottraux et al, 1990;De Kleine, Hendriks, Kusters, Broekman, & van Minnen, 2012;Hoexter et al, 2013;Nordgreen et al, 2012;Taylor, 2003). We also set out to exclude studies that solely investigated disorder-specific moderators and to report only the transdiagnostic (relevant to multiple anxiety disorders) moderators in studies that examined both disorder-specific (e.g., type of social anxiety disorder, Hedman et al, 2012;dominance of obsessions vs. compulsions, Hohagen et al, 1998;presence of hoarding, Maher et al, 2010) and transdiagnostic moderators.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…disorder severity, sociodemographic characteristics) in order to allow for conclusions to be drawn across multiple anxiety disorders. Based on these criteria, we excluded papers that measured variables after baseline (Burton, Schmertz, Price, Masuda, & Anderson, 2013;Rodebaugh, Heimberg, Schultz, & Blackmore, 2010) or only conducted withingroup analyses (Andersson, Carlbring, & Grimlund, 2008;Brody et al, 1998;Cottraux et al, 1990;De Kleine, Hendriks, Kusters, Broekman, & van Minnen, 2012;Hoexter et al, 2013;Nordgreen et al, 2012;Taylor, 2003). We also set out to exclude studies that solely investigated disorder-specific moderators and to report only the transdiagnostic (relevant to multiple anxiety disorders) moderators in studies that examined both disorder-specific (e.g., type of social anxiety disorder, Hedman et al, 2012;dominance of obsessions vs. compulsions, Hohagen et al, 1998;presence of hoarding, Maher et al, 2010) and transdiagnostic moderators.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Research on efficacy of videotaped feedback for social anxiety demonstrated the saliency of videotaping as an anxiety provoking event that activates negative self perceptions (e.g., Rodebaugh & Rapee, 2005;Rodebaugh, Heimberg, Schultz, & Blackmore, 2010). Videotaped feedback has been successfully used to improve the valence of self ratings of performance in socially anxious individuals (Harvey, Clark, Ehlers, & Rapee, 2000;Kim, Lundh, & Harvey, 2002;Morgan & Banerjee, 2006;Parr & Cartwright-Hatton, 2009;Rapee & Hayman, 1996;Rodebaugh, 2004;Rodebaugh & Chambless, 2002;Rodebaugh & Rapee, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In using video feedback, clients fi rstly identify what they expect to see in their social performance, complete the task while being video recorded, and then observe their performance as objectively as possible. Although there is mixed evidence (Ramos et al 2008 ;Smits et al 2006 ), video feedback has been found to add benefi t to treatment for social anxiety in adults (Rodebaugh et al 2010 ) and reduce anticipatory anxiety in adolescents (Parr and Cartwright-Hatton 2009 ). Studies comparing CBT enhanced with both attention retraining and video feedback to standard CBT programmes have found significantly better outcomes for adults with SAD using the enhanced CBT (Rapee et al 2009 ).…”
Section: ) the Original Intervención En Adolescentes Con Fobia Socialmentioning
confidence: 99%